2013
DOI: 10.12988/ija.2013.3763
|View full text |Cite
|
Sign up to set email alerts
|

Some refinements of Gersgorin discs

Abstract: This paper refines the work on Geršgorin Discs in the article "Geometric Multiplicities and Geršgorin Discs", The American Mathematical Monthly, 120(2013), 452-455 by R. Marsli and F. Hall. Some consequences of this refinement and examples are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Varga's nice book [31] surveys various applications and extensions of this important theorem. Recently, Marsli and Hall [25] found an interesting result, which states that if λ is an eigenvalue of an n × n matrix A with geometric multiplicity k, then λ is in at least k of the n Gerŝgorin discs of A. Fiedler et al [12] proved that for a triple of positive integers k, r, t with k ≤ r ≤ t, there is a t × t complex matrix A and an eigenvalue λ of A such that λ has geometric multiplicity k and algebraic multiplicity t, and λ is in precisely r Gerŝgorin discs of A. Marsli and Hall extended these results in subsequent papers [24,26,27]. Bárány and Solymosi [6] showed that if the matrix entries are non-negative and an eigenvalue has geometric multiplicity at least two, then this eigenvalue lies in a smaller disk.…”
mentioning
confidence: 95%
“…Varga's nice book [31] surveys various applications and extensions of this important theorem. Recently, Marsli and Hall [25] found an interesting result, which states that if λ is an eigenvalue of an n × n matrix A with geometric multiplicity k, then λ is in at least k of the n Gerŝgorin discs of A. Fiedler et al [12] proved that for a triple of positive integers k, r, t with k ≤ r ≤ t, there is a t × t complex matrix A and an eigenvalue λ of A such that λ has geometric multiplicity k and algebraic multiplicity t, and λ is in precisely r Gerŝgorin discs of A. Marsli and Hall extended these results in subsequent papers [24,26,27]. Bárány and Solymosi [6] showed that if the matrix entries are non-negative and an eigenvalue has geometric multiplicity at least two, then this eigenvalue lies in a smaller disk.…”
mentioning
confidence: 95%
“…In particular, the following result was proved in [3]. More recently, we obtained a refinement of Theorem 1.1 in [5]. Theorem 1.2.…”
Section: Geršgorin Theorem Let a ∈ M N And Letmentioning
confidence: 82%
“…The next theorem is a generalization of Theorem 3.9 in [5] Theorem 2.7. Let A ∈ M n and let • be a matrix norm.…”
Section: Remark 26 Corollary 24 Provides An Algorithm That May Detmentioning
confidence: 92%
See 2 more Smart Citations